Poetry and the expectation of the border - Smith, Lytton (Frontiers in Human Dynamics, 2023)
This essay explores a set of poetic texts—the Transborder Immigrant Tool (TBT); Amy Sara Carroll’s “The Desert Survival Series/La serie de sobrevivencia del desierto”; and Claudia Rankine and John Lucas’s video poem “Zidane” and the version of that poem included in Rankine’s book Citizen—against the backdrop of recent United States Customs and Border Protection investment in autonomous surveillance towers, the development of the “100 mile” expanded border region, and 2022 practices by Republican governors to relocated migrants to the U.S. to Democrat states. I argue for the existence in poetry of what I term “the expectation of the border”: the moment when we name the border not as a graspable and unchangeable line in physical space and legal jurisdiction, but as a conceptual reckoning with definitions of community, including but not limited to citizenship status. Drawing on citizenship theorist Engin Isin’s argument that “poetic articulation” especially “captures the essence of the political,” this paper suggests poetry as a specialized intervention in border politics and definitions of citizenship, including the conditions of the “hostile environment.”